2008
DOI: 10.1113/expphysiol.2007.040261
|View full text |Cite
|
Sign up to set email alerts
|

Injections of angiotensin‐converting enzyme 2 inhibitor MLN4760 into nucleus tractus solitarii reduce baroreceptor reflex sensitivity for heart rate control in rats

Abstract: Injections of the angiotensin(1-7) [Ang(1-7)] antagonist [D-Ala7 ]-Ang(1-7) into the nucleus of the solitary tract (NTS) of Sprague-Dawley rats reduce baroreceptor reflex sensitivity (BRS) for control of heart rate by ∼40%, whereas injections of the angiotensin II (Ang II) type 1 receptor antagonist candesartan increase BRS by 40% when reflex bradycardia is assessed. The enzyme angiotensin-converting enzyme 2 (ACE2) is known to convert Ang II to Ang(1-7). We report that ACE2 activity, as well as ACE and nepril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
73
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 47 publications
10
73
1
Order By: Relevance
“…Overexpression of ACE2 in the brain reduces hypertension by improving the arterial baroreflex and autonomic function in hypertensive animals (37,38). Injection of the ACE2 inhibitor MLN-4760 into the NTS reduces the baroreceptor reflex sensitivity for HR control in rats (6). Our data show that the basal RSNA in CHF rats is significantly higher than that in sham rats.…”
Section: Discussionsupporting
confidence: 52%
“…Overexpression of ACE2 in the brain reduces hypertension by improving the arterial baroreflex and autonomic function in hypertensive animals (37,38). Injection of the ACE2 inhibitor MLN-4760 into the NTS reduces the baroreceptor reflex sensitivity for HR control in rats (6). Our data show that the basal RSNA in CHF rats is significantly higher than that in sham rats.…”
Section: Discussionsupporting
confidence: 52%
“…ACE2 and neprilysin mRNAs were significantly higher in the old treated group compared with the old group, while ACE mRNA declined with age but was restored with the AT 1 receptor blockade. We previously showed that ACE2 is the major ANG-(1-7) processing enzyme in dorsomedial medulla (9). There was no difference in AT 1a receptor mRNA expression between the groups, but AT 1b mRNA was significantly increased in the old treated group.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, we (18,51) have shown that ExT improves the sympathoexcitatory drive from the PVN by normalization of the glutamatergic and angiotensinergic drives to sympathoexcitation in rats with HF. Recently, the role of the nonclassical pathway of renin-angiotensin system genes such as angiotensin-converting enzyme 2 and the Mas receptor in the central nervous system and their participation in central sympathetic activation have been also been widely addressed (6,7,17,45). Changes in these inhibitory pathways may also be involved in the improvement of the central component of the baroreflex in rats with HF, but this remains to be examined.…”
Section: Discussionmentioning
confidence: 95%